Analysis of the rational tafsir of Q.S. Al-Baqarah verse 164 on the signs of Allah’s power in Tafsir Al-Manar by Muhammad ‘Abduh and Rasyid Rida - Vera Siska; Janna Aulia; Hidayatullah Ismail (Privietlab, 2025)
This study discusses the rational interpretation of Q.S. al-Baqarah verse 164 concerning the signs of Allah’s power in Tafsir al-Manār by Muhammad ‘Abduh and Rasyid Rida. This study is motivated by the need to understand the relationship between revelation and scientific reality within the framework of modern Qur’anic exegesis. Muhammad ‘Abduh and Rasyid Rida employed a rational (‘aqli) approach in interpreting verses related to natural phenomena, emphasizing the role of reason and scientific observation in recognizing the greatness of Allah. This study adopts a library research method, using Tafsir al-Manār as the primary source, supported by relevant books, journals, and academic articles as secondary references. The analysis is conducted descriptively and analytically to identify the interpretive principles (qawā‘id al-tafsīr) applied by the exegetes, including al-Tafsīr bi al-Qur’ān, al-Tafsīr bi al-‘Aql, al-Tafsīr bi al-Wāqi‘, and al-Tawḥīd wa al-Tajdid. The results show that Tafsir al-Manār interprets natural phenomena such as the heavens, the earth, rain, and wind not merely as physical realities but as āyāt kauniyyah (cosmic signs) that guide human beings to think and strengthen their faith. Revelation and science are viewed as complementary, not contradictory, in affirming Allah’s oneness and wisdom.